Odpowiedź :
a) 2x-5=3
2x=8, x=4
b)-3x+6=7
-3x=1
x=-1/3
c)2x-5=x+3
x=8
d) mnożymy na ukos
(x-3)*2= 3x
2x-6=3x
x=-6
e)2x+4=7x-3
-5x=-7
x=7/5
f) (x+2)*2=10x
2x+4=10x
8x=4
x= 1/2 Pozdrawiam
2x=8, x=4
b)-3x+6=7
-3x=1
x=-1/3
c)2x-5=x+3
x=8
d) mnożymy na ukos
(x-3)*2= 3x
2x-6=3x
x=-6
e)2x+4=7x-3
-5x=-7
x=7/5
f) (x+2)*2=10x
2x+4=10x
8x=4
x= 1/2 Pozdrawiam
Odpowiedź:
a)
2x - 5 = 3
2x = 3 + 5 /:2
x = 8/2 = 4
b)
-3(x - 2) = 7
-3x + 6 = 7
-3x = 7 - 6 /:(-3)
x = -1/3
c)
2x - 5 = x + 3
2x - x = 3 + 5
x = 8
d)
(x - 3)/3 = x/2
1/3x - 1 = 1/2x
1/3x - 1/2x = 1
2/6x - 3/6x = 1
-1/6x = 1 /*(-6)
x = -6
e)
2x + 4 = 7x - 3
2x - 7x = -3 - 4
-5x = -7 /:(-5)
x = 7/5 = 1 2/5
f)
(x + 2)/5 = 2x/2
1/5x + 2/5 = x
3/5x - x = -2/5
-2/5x = -2/5 /*(-5/2)
x = 2/5 * 5/2 = 1
Szczegółowe wyjaśnienie: